The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.yfrne.2020.100836
|View full text |Cite
|
Sign up to set email alerts
|

Physiopathological role of the enzymatic complex 5α-reductase and 3α/β-hydroxysteroid oxidoreductase in the generation of progesterone and testosterone neuroactive metabolites

Abstract: The enzymatic complex 5α-reductase (5α-R) and 3α/3β-hydroxysteroid oxidoreductase (HSOR) is expressed in the nervous system, where it transforms progesterone (PROG) and testosterone (T) into neuroactive metabolites. These metabolites regulate myelination, brain maturation, neurotransmission, reproductive behavior and the stress response. The expression of 5α-R and 3α-HSOR and the levels of PROG and T reduced metabolites show regional and sex differences in the nervous system and are affected by changing physio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 348 publications
0
14
0
1
Order By: Relevance
“…Both steroid hormones and neurosteroids, which are both found in the nervous system, are collectively referred to as neuroactive steroids and are important physiological regulators of nervous system functioning [23]. In particular, DHP controls reproductive functions, as well as glutamatergic and GABAergic neurotransmission [24], whereas isoallopregnanolone influences the lipid bilayer model system containing cholesterol [25,26]. In the brain, androgen molecules have been shown to regulate dendritic spine maturation [27,28], behaviour [29,30], neurite growth [31], neurogenesis and neuronal survival [32], apoptosis [33] and catecholamine production [34].…”
Section: Introductionmentioning
confidence: 99%
“…Both steroid hormones and neurosteroids, which are both found in the nervous system, are collectively referred to as neuroactive steroids and are important physiological regulators of nervous system functioning [23]. In particular, DHP controls reproductive functions, as well as glutamatergic and GABAergic neurotransmission [24], whereas isoallopregnanolone influences the lipid bilayer model system containing cholesterol [25,26]. In the brain, androgen molecules have been shown to regulate dendritic spine maturation [27,28], behaviour [29,30], neurite growth [31], neurogenesis and neuronal survival [32], apoptosis [33] and catecholamine production [34].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, gene expression levels for enzymes related to metabolism of DHP and ALLO also appeared to compensate for decreased levels of these steroids as a result of gonadectomy. Indeed, we here reported that the gene expression of the 5-alpha-reductase (i.e., enzyme converting PROG into DHP) [ 68 ] was upregulated in a sexually dimorphic way, depending on the isoforms considered. Gonadectomy induced an increase in the gene expression of type 1 only in females, and of type 2 only in males.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we recently observed that rat colon expresses steroidogenic capability and, in particular, an high production of a T metabolite, such as the 3α-diol [ 71 ]. It is important to note that this androgen metabolite, like THP, is able to interact with GABA-A receptors [ 72 ] and its levels are affected in PFS patients as well as in its experimental model [ 14 , 21 , 22 , 28 ]. This may further support the hypothesis of a role of steroids interacting with GABA-A receptors in the pathogenesis of PFS.…”
Section: Discussionmentioning
confidence: 99%